2023
DOI: 10.1021/acsabm.2c01019
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Extracellular Vesicle-Encapsuled Nanoreactors for Effective Targeting and Cascade Killing of Cancer Cells

Abstract: Nanomaterials have presented great potential for cancer therapy. However, their therapeutic efficacy is not always satisfied because of inefficient biocompatibility and targeting efficacy. Here, we report engineered extracellular vesicle (EV)-encapsuled nanoreactors for the targeting and killing of cancer cells. EVs are extracted from engineered cancer cells with surface N-glycans cut and intracellular microRNA-21 (miR-21) silenced to generate cancer-targeting membranes for the following coating of gold–polydo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Wu et al reported extracellular vesicles encapsulated nanoreactor for the precise targeting and killing of cancer cells. [111] Their results showed that nanoreactor-targeted delivery to cancer cells significantly enhances the therapeutic effect, in which the killing rate up to 90% under laser irradiation. Furthermore, the nanoreactor could effectively inhibit the proliferation of cancer cell spheres, indicating good potential for improving combination therapy.…”
Section: Nanoreactors Developed Based On Polymer Vesiclesmentioning
confidence: 99%
“…Wu et al reported extracellular vesicles encapsulated nanoreactor for the precise targeting and killing of cancer cells. [111] Their results showed that nanoreactor-targeted delivery to cancer cells significantly enhances the therapeutic effect, in which the killing rate up to 90% under laser irradiation. Furthermore, the nanoreactor could effectively inhibit the proliferation of cancer cell spheres, indicating good potential for improving combination therapy.…”
Section: Nanoreactors Developed Based On Polymer Vesiclesmentioning
confidence: 99%
“…The therapeutic expectation from surgery, radiotherapy, and chemotherapy for CRC is not so much significant and has multiple complications after treatment. Therapeutic approach based on exosomes is very efficient in cancer treatment. , High chemo exposure and CRC-derived exosomes miRNA-24 lead to the development of chemoresistance and stem cells of cancer cells. , Colon cancer stem cells (CSCs) are responsible for cancer recurrence even after treatment. However, it has also been shown that survivability can be improved by targeted therapy to eradicate CSCs .…”
Section: Exosome-based Therapeutic Approach For Crcmentioning
confidence: 99%
“…These nanoreactors have a variety of components that allow them to provide chemotherapeutic reagents, photothermal therapy sensitization, starvation therapy, and the generation of reactive oxygen species. When delivered in an EV without laser irradiation, they successfully destroyed 80% of cancer cells inside a 3D cancer cell sphere, and with laser irradiation, the cytotoxicity of cancer cells increased to 90% [113]. Future research should look to adapt these EV nanoreactors to be used in mouse models.…”
Section: Further Research and Perspectivesmentioning
confidence: 99%